Analytical and numerical study of composite twin-girder bridge decks with adhesive connectors and composite reinforcement - Rabia, Benferhat; Tahar, Hassaine Daouadji; Boussad, Abbes; Tayeb, Bensatallah; Abderezak, Rabahi; Fazilay, Abbes (Coupled Systems Mechanics, 2025)
This study conducts both analytical and numerical investigations of composite twin-girder bridge decks. It combines numerical solution with analytical solutions to assess the structural behavior. Traditional steel shear connectors are replaced by adhesives, with a focus on the interfacial slip caused by this innovative assembly method. The study also evaluates the interfacial stresses in the steel girders, which are strengthened with composite materials to improve structural performance. The results demonstrate that a bracing system combining crossed diagonals and two parallel bars effectively reduces interfacial slip and stresses, thereby enhancing the stability and durability of composite twin-girder bridge decks.